Brook trout (Salvelinus fontinalis) movement and survival after removal of two dams on the West Branch of the Wolf River, Wisconsin. Issue 2 (28th November 2019) - Easterly, Emma G.; Isermann, Daniel A.; Raabe, Joshua K.; Pyatskowit, Joshua W.
Abstract: Dam removals allow fish to access habitats that may provide ecological benefits and risks, but the extent of fish movements through former dam sites has not been thoroughly evaluated for many species. We installed stationary PIT antennas in 2016 and 2017 to evaluate movements and survival of brook trout Salvelinus fontinalis in the West Branch of the Wolf River (WBWR) in central Wisconsin following removal of two dams and channel modifications designed to promote fish movement. These changes provided access to lacustrine habitats that might provide suitable winter habitat or act as ecological sinks. We used multistate models to estimate transition probabilities between river sections, to determine whether brook trout: (a) moved between multiple river sections and (b) entered lacustrine habitats as seasonal refuges, but eventually returned to lotic habitat. We also used a Cormack‐Jolly‐Seber model to evaluate whether apparent survival of brook trout in the WBWR was comparable to other populations. Few fish moved among river sections or used lacustrine habitat (<5% of tagged fish); most brook trout remained in sections where they were initially tagged, potentially due to quality habitat located throughout the river. Like other studies, brook trout in the WBWR appear to experience high mortality based on low number of detections, few physical recaptures and an estimated eight‐month apparent survival rate of 0.27. In scenarios where fish can already access suitable habitat, removal of dams may not result in substantial increases in fish movement and colonisation of newly accessible habitat may not occur immediately.